Green Tourism Village Tourism Model Based on Bali Cultural Environment Law - Sugiartha, I Nyoman Gede; Widyantara, I Made Minggu; Suryani, Luh Putu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The concept of green tourism is a debate in its implementation. This concept puts forward the sustainability of an event based on Balinese cultural environmental law in supporting sustainable development. This is in line with the Roadmap for Leading Research Center for Research and Community Service (P3M) of Warmadewa University, namely the Environment with the topic of Ecotourism research based on environmental law. The concept of a tourism village is a form of community-based tourism that aims to improve the welfare of the people in the area. Miles and Huberman's model was used as data analysis. A SWOT analysis was also carried out to determine the potential of a tourist village in terms of three pillars, namely the concept of green, law, and culture. Currently, most of the tourist villages in Bali Province have not succeeded in developing properly. One of the problems is that people are confused about applying environmental law and their culture in conducting events. The research aimed to develop a model of green tourism village tourism based on Balinese cultural environmental law to improve environmental law compliance, at the event. This also helps increase the trust of guests in tourist villages because they are legally protected by the products purchased and ultimately have an impact on guests to buy event services, as well as improving people's living standards. This research is to produce a tourism village green tourism model based on Balinese cultural environmental law so that it can increase green reputation as a strategy in increasing tourism village income which leads to the welfare of the surrounding community sustainably. While the additional purpose of the results of this study is to be able to provide recommendations for the Bali provincial government and related parties regarding green tourism in tourist villages.